2017
DOI: 10.14411/fp.2017.031
|View full text |Cite
|
Sign up to set email alerts
|

Feeding strategies and competition between terrestrial Haemadipsa leeches (Euhirudinea: Arhynchobdellida) in Danum Valley rainforest (Borneo, Sabah)

Abstract: Abstract:Haemadipsid leeches are among the most successful terrestrial invertebrates in Bornean rainforests. They are very common ectoparasites of vertebrates, and their abundance has facilitated the conduction of numerous projects in the fields of ecology, zoogeography and taxonomy. We undertook research on two species inhabiting lowland dipterocarp forest, Haemadipsa picta Moore, 1929 and Haemadipsa subagilis (Moore, 1929), in order to address the following questions: (a) is there a difference in leech abund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(37 citation statements)
references
References 24 publications
2
35
0
Order By: Relevance
“…Leeches were consistent in their ambush site preferencesindividuals that chose higher ambush positions under natural conditions also chose higher ambush positions on our model plants in the experiment (regression analysis: F 1,165 = 15.5, Pearson r = 0.29, P < 0.0002; Spearman's correlation analysis: R = 0.30, P < 0.00001), although the HAPs under natural conditions explained only 8% of the variance in the HAPs in the experiment. Overall, in accordance with Gąsiorek & Różycka (2017), our findings from the natural and experimental conditions indicate that H. picta leeches actively choose hunting locations according to their above-ground height and shift their ambush sites to higher foliage over ontogeny.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…Leeches were consistent in their ambush site preferencesindividuals that chose higher ambush positions under natural conditions also chose higher ambush positions on our model plants in the experiment (regression analysis: F 1,165 = 15.5, Pearson r = 0.29, P < 0.0002; Spearman's correlation analysis: R = 0.30, P < 0.00001), although the HAPs under natural conditions explained only 8% of the variance in the HAPs in the experiment. Overall, in accordance with Gąsiorek & Różycka (2017), our findings from the natural and experimental conditions indicate that H. picta leeches actively choose hunting locations according to their above-ground height and shift their ambush sites to higher foliage over ontogeny.…”
supporting
confidence: 88%
“…Only a few studies that have focused on the ecology of these animals are available in the literature (Fogden & Proctor 1985, Kendall 2012, Smythies 1959). According to a recent observational study, H. picta co-occurs in parts of Bornean forests with its potential competitor and close relative, Haemadipsa subagilis, but the two species differ in their distribution patterns at the microscale (Gąsiorek & Różycka 2017). Specifically, H. picta leeches become less abundant with increasing distance from animal trails, and larger individuals are more frequently found on higher foliage.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These have distinct morphological and behavioral characteristics that allow their separation in the field (Figure 1). Previous work in Borneo has suggested that the tiger leech favors degraded forest habitat (i.e., encounter rate increases with declining forest quality), whereas the brown leech favors intact forest habitats (Kendall, 2012), and a similar difference in microhabitat use was shown along trails in primary forest, with the tiger leech more commonly found at the edges of trails, and above ground level, than the brown leech (Gąsiorek & Różycka, 2017). The brown leech has a more specialized habitat, in the leaf litter compared to the tiger leech (Gąsiorek & Różycka, 2017).…”
Section: Introductionmentioning
confidence: 89%
“…It is difficult to examine the selectivity of the leeches in that study because the mammal diversity is much higher than in Yakushima. The feeding strategy of leeches can vary with the species even within the same genus (Gasiorek & Rozycka, ), as well as with the behavior of the host animals, such as strata use (Reed & Bidner, ). Much more study would be needed to generalize the findings on the preferred and avoided host taxa of leeches.…”
Section: Discussionmentioning
confidence: 99%